RIWAYAT STATUS IMUNISASI DASAR BERHUBUNGAN DENGAN KEJADIAN BALITA STUNTING - Yosintha Dilina Wanda; Fardila Elba; Didah Didah; Ari Indra Susanti; Fedri Ruluwedrata Rinawan (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background: According to the World Health Organization (WHO) 2018, the prevalence of stunting in Indonesia is the third country with the highest prevalence in the Southeast Asia Region (SEAR). The average prevalence of children under five in Indonesia in 2005-2017 was 36.4%. In West Java the incidence of stunting is 29.9% and in Sumedang Regency the figure is still quite high at 36%, and based on data from the Jatinangor Health Center in 2020 there are 60 stunting toddlers.Purpose: The purpose to analyze the relationship between the history of basic immunization status and the incidence of in toddler in Hegarmanah Village, Jatinangor District in 2020.Methods: This research design is a quantitative research conducted in Hegarmanah Village in November. This study use a case control design with a ratio of 1:1. The case group of this study was stunting and the control group was non-stunted. The groups of stunting and non-stunted toddlers were determined by a matching system of age and gender categorization. Sampling used proportionate stratified random technique. The sample in this study were stunted and non-stunted toddlers with a total sample of 120 respondents, 60 case groups and 60 control groups. The research instrument is a questionnaire and a microtoise to measure height. Bivariate analysis was carried out with Chi-Square and Odds Ratio testsResults: The results showed that 30 (25%) stunting toddlers aged 24-<36 months, 23 (19%) toddlers aged 24-<36 months and 19 (16%) boys with a history of incomplete basic immunization status . Bivariate analysis was carried out with Chi-Square and Odds Ratio tests with a 95% confidence level obtained (p = 0.000) with OR and CI (4.958 (2.074-11.852)). This states that there is a relationship between the history of basic immunization status on the incidence of stunting under five in Hegarmanah Village, Jatinangor District.Conclusion: There is a relationship between the history of basic immunization status on the incidence of stunting in toddlers in Hegarmanah Village, Jatinangor District with a value of p<0.05 (p=0.00<0.05) and there is a risk of stunting in toddlers with incomplete immunization 4.9 times compared to toddlers with complete immunization.Suggestion Future researchers are expected to be able to further investigate what types of immunization can affect stunting. Keywords: Relationship, Stunting, Basic Immunization, Toddler ABSTRAK Latar Belakang: Menurut World Health Organization (WHO) data prevalensi kejadian stunting Indonesia termasuk negara ketiga dengan prevalensi tertinggi di regional Asia Tenggara /South-East Asia Regional (SEAR). Rata-rata prevalensi balita di Indonesia tahun 2005-2017 adalah 36,4%. Di Jawa Barat angka kejadian stunting yaitu 29,9% dan di Kabupaten Sumedang angkanya masih cukup tinggi yaitu sebesar 36%, dan berdasarkan data Puskesmas Jatinangor pada tahun 2020 terdapat 60 balita stunting.Tujuan: Menganalisis hubungan riwayat status imunisasi dasar dengan kejadian balita stunting di Desa Hegarmanah Kecamatan Jatinangor Tahun 2020.Metode: Rancangan penelitian ini merupakan penelitian kuantitatif yang dilakukan di Desa Hegarmanah pada Bulan November. Penelitian ini menggunakan desain case control dengan perbandingan 1:1. Kelompok kasus penelitian ini yaitu stunting dan kontrol yaitu non stunting. Kelompok balita stunting dan non stunting ditentukan dengan sistem matching kategorisasi usia dan jenis kelamin. Pengambilan sampel menggunakan teknik proportionate stratified random. Sampel dalam penelitian ini adalah balita yang stunting dan non stunting dengan jumlah sampel 120 responden, sebanyak 60 kelompok kasus dan 60 kelompok kontrol. Instrumen penelitian ini yaitu kuisioner dan microtoise untuk mengukur tinggi badan. Analisis bivariate dilakukan uji Chi-Square dan Odds RatioHasil: Hasil penelitian didapatkan 30 (25%) balita stunting dengan usia 24-<36 bulan, 23 (19%) balita usia 24-<36 bulan dan 19 (16%) balita laki-laki dengan riwayat status imunisasi dasar yang tidak lengkap. Analisis bivariate dilakukan uji Chi-Square dan Odds Ratio dengan tingkat kepercayaan 95% didapatkan (p=0,000) dengan OR dan CI (4,958 (2,074-11,852)).Kesimpulan: Terdapat hubungan antara riwayat status imunisasi dasar pada kejadian balita stunting di Desa Hegarmanah Kecamatan Jatinangor dengan nilai p<0,05 (p=0.00<0.05) serta terdapat risiko kejadian stunting pada balita dengan imunasi tidak lengkap 4,9 kali dibanding balita dengan imunisasi yang lengkap.Saran Peneliti selanjutnya diharapkan dapat meneliti lebih lanjut mengenai jenis imunisasi apa yang dapat mempengaruhi stunting. Kata kunci : Hubungan, Stunting, Imunisasi Dasar, Balita